Hot Spots of Crime Are Not Just Hot Spots of Crime: examining Health Outcomes at Street Segments - Weisburd, David (Journal of contemporary criminal justice, 2019)
In this article, we seek to identify whether the relationship between health disparities and crime occurs at a micro-geographic level. Do hot spot streets evidence much higher levels of mental and physical illness than streets with little crime? Are residents of crime hot spots more likely to have health problems that interfere with their normal daily activities? To answer these questions, we draw upon a large National Institutes of Health study of a sample of hot spots and non-hot spots in Baltimore, Maryland. This is the first study we know of to report on this relationship, and accordingly, we present unique descriptive data. Our findings show that both physical and mental health problems are much more likely to be found on hot spot streets than streets with little crime. This suggests that crime hot spots are not simply places with high levels of crime, but also places that evidence more general disadvantage. We argue that these findings have important policy implications for the targeting of health services and for developing proactive prevention programs.